2021
DOI: 10.3390/v13020276
|View full text |Cite
|
Sign up to set email alerts
|

VOC 202012/01 Variant Is Effectively Neutralized by Antibodies Produced by Patients Infected before Its Diffusion in Italy

Abstract: The coronavirus disease 2019 (Covid-19) pandemic is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and presents a global health emergency that needs urgent intervention. Viruses constantly change through mutation, and new variants of a virus are expected to occur over time. In the United Kingdom (UK), a new variant called B.1.1.7 has emerged with an unusually large number of mutations. The aim of this study is to evaluate the level of protection of sera from 12 patients infected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The SARS-CoV-2 lineage 20I/501Y.V1 seems to be covered by the available vaccines. A recent Italian study by Rondinone et al [32] has indicated a high level of cross-lineage reactivity between the previously circulating strains and 20I/501Y.V1 lineage. In particular, all tested samples from the previously infected patients (n = 12) developed neutralizing antibody titers of 1:160-1:320 against the novel 20I/501Y.V1 lineage and these latter were the same as those against the previously circulating variant.…”
Section: Discussionmentioning
confidence: 94%
“…The SARS-CoV-2 lineage 20I/501Y.V1 seems to be covered by the available vaccines. A recent Italian study by Rondinone et al [32] has indicated a high level of cross-lineage reactivity between the previously circulating strains and 20I/501Y.V1 lineage. In particular, all tested samples from the previously infected patients (n = 12) developed neutralizing antibody titers of 1:160-1:320 against the novel 20I/501Y.V1 lineage and these latter were the same as those against the previously circulating variant.…”
Section: Discussionmentioning
confidence: 94%
“…The purified mAbs showed a spike S1/S2 binding activity of 103 and 81 AU/mL at a 1:2 dilution in the diasorin test. They were then tested by microneutralization assay, using three different Italian SARS-CoV-2 viral isolates belonging to Clades G and O and the lineage B1.1.7 U.K. [ 14 ]. The two anti-spike mAbs did not show any measurable neutralizing activity even at the highest concentration tested of 0.5 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The purified mAbs were tested for neutralization using three virus strains: Clade G VR10734 (S-D614G mutant, hCoV-19/Italy/LOM-INMI-10734/2020; GISAID Accession ID: EPI_ISL_568579), Clade O (2019-nCoV/Italy-INMI1; GISAID accession ID EPI_ISL_410546), and VOC 202012/01 (hCoV-19/Italy/CAM-INMI-118/2020; GISAID Accession ID: EPI_ISL_736997; Lineage B1.1.7) with serial dilution of purified antibody from the two positive clones (0.5 mg/mL to 0.5 ng/mL) according to published procedures [ 14 ]. Briefly, mAbs were diluted in serum-free medium and titrated in duplicate in ten-fold dilutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the beginning of the COVID-19 pandemic, several studies have reported genomic sequence variations of SARS-CoV-2 isolates (Leung et al 2021;Martin et al 2021;Rondinone et al 2021;Tegally et al 2021a;Tegally et al 2021b). Among these genetic variations, a single nucleotide polymorphism (SNP) found at position 8,782 (in orf1ab; C instead of T) of SARS-CoV-2 genomic sequence is a hallmark of the L strain (Tang et al 2020), whereas the unaltered nucleotide is found at the same position in the S strain.…”
Section: Introductionmentioning
confidence: 99%